2006
DOI: 10.1007/s00253-005-0287-0
|View full text |Cite
|
Sign up to set email alerts
|

High-level production of bioactive human beta-defensin-4 in Escherichia coli by soluble fusion expression

Abstract: Human beta-defensin-4 (hBD4) is a cationic 50-amino acid antimicrobial peptide with three conserved cysteine disulfide bonds. It exhibits a broad antimicrobial spectrum. This study describes the synthesis of hBD4 gene, the heterologous fusion expression of the peptide in Escherichia coli, and the bioactive assay of released hBD4. A PCR-based gene SOEing (splicing by overlap extension) synthesis method was used in the synthesis of the hBD4 gene with optimized codons. By constructing the expression plasmid (pET3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 31 publications
2
47
1
2
Order By: Relevance
“…The final concentration of IPTG plays an important role in regulating the expression level of recombinant proteins because of its negative effects on cell growth (Xu et al 2006). In this study, four different concentrations of IPTG (0.4, 0.6, 0.8, and 1.0 mM) were examined, and the SDS-PAGE results are shown in Fig.…”
Section: Iptg Concentrationmentioning
confidence: 99%
“…The final concentration of IPTG plays an important role in regulating the expression level of recombinant proteins because of its negative effects on cell growth (Xu et al 2006). In this study, four different concentrations of IPTG (0.4, 0.6, 0.8, and 1.0 mM) were examined, and the SDS-PAGE results are shown in Fig.…”
Section: Iptg Concentrationmentioning
confidence: 99%
“…Although hBD5 and hBD6 have shown antimicrobial activity, they are not expressed in the respiratory epithelium (218)(219)(220). hBD1 is constitutively expressed in the epithelium, whereas hBD2, -3, and -4 can be induced by a variety of bacterial, fungal, and viral pathogens (221)(222)(223)(224)(225)(226)(227).…”
Section: Antimicrobial Productsmentioning
confidence: 99%
“…To our knowledge, there are no reports about non-optimized Gn expression in insect cells, but some studies have shown that high-level expression of recombinant proteins is affected by factors such as the different codon preferences in different expression systems, and codon optimization can significantly increase the expression level [53][54][55][56]. This is the first report on the cloning and expression of CCHFV Gn glycoprotein in a baculovirus expression system.…”
Section: Discussionmentioning
confidence: 84%